Mutagenicity assessment of aerosols in emissions from wood combustion - Binh Ngan Vu (2012)
Polycyclic aromatic hydrocarbon (PAH) extracts of PM2.5 collected from combustion of seven wood species and briquettes were tested for mutagenic activities using Ames test with Salmonella typhimurium TA98 and TA100. The woods werePinuspinaster (maritime pine), Eucalyptus globulus (eucalypt), Quercussuber (cork oak), Acacia longifolia (golden wattle), Quercusfaginea (Portuguese oak), Oleaeuropea (olive), and Quercus ilex rotundifolia (Holm oak). Burning experiments were done using woodstove and fireplace, hot start and cold start. A mutagenic/weak mutagenic response was recorded for all species except golden wattle. The extracts with indirect acting mutagenicity were mainly obtained from fireplace and cold start conditions. The strong mutagenic extracts were not correlated with high emission factors of carcinogenic PAHs. Several samples were weak mutagens at low concentration of PAHs. The negative result recorded for the golden wattle extracts is positive since after confirmation, this species can be recommended for domestic use.